Simulasi Sistem Dinamik Model Matematika Kasus Kecanduan Bermain Gadget Bagi Anak Usia Dini dengan Faktor Pengawasan Orang Tua - Pratama, Muhammad Isbar; Lismayani, Angri (Journal of Mathematics, Computations and Statistics, 2023)
This research aims to develop a mathematical model to depict the changes in the level of gadgetaddiction in early childhood of the SEAR type (Susceptible - Exposed - Addicted - Recovered). Themathematical model created is then analyzed for its stability. After the stability analysis, the model is furthersubjected to simulation using Maple 18 software. The simulation is performed three times with differentvalues of parental supervision factors, namely 0.0084, 0.5217, and 0.8214. The simulation results indicatethat the higher the level of parental supervision, the faster the cases of gadget addiction in early childhooddecline.